2021
DOI: 10.3390/cancers13071607
|View full text |Cite
|
Sign up to set email alerts
|

Response Prediction in Immune Checkpoint Inhibitor Immunotherapy for Advanced Hepatocellular Carcinoma

Abstract: Immune checkpoint inhibitors (ICI) have been applied to treat advanced stage hepatocellular carcinoma (HCC) and obtain promising effects. However, tumor response to treatment was unpredictable. A predicting biomarker of objective response or disease-control is an unmet need for patient selection. In this study, 45 advanced HCC patients who failed to sorafenib treatment and received nivolumab, 3 mg/kg bi-weekly, were included. Tumor responses to nivolumab treatment were assessed by the modified response evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Bagley et al analyzed 175 patients with advanced non-small cell lung cancer treated with nivolumab and found that pretreatment NLR > 5 was significantly associated with inferior OS and PFS [10]. With regard to ICI therapy for HCC, Hung et al reported that NLR ≤ 2.5 was a useful predictor of response to SD or better in 45 patients treated with nivolumab monotherapy, which is similar to our report [19]. On the other hand, Dharmapuri et al reported that NLR after three cycles of nivolumab treatment was more strongly associated with the response and OS prolongation compared with NLR before treatment in 103 patients with HCC treated with nivolumab.…”
Section: Discussionsupporting
confidence: 88%
“…Bagley et al analyzed 175 patients with advanced non-small cell lung cancer treated with nivolumab and found that pretreatment NLR > 5 was significantly associated with inferior OS and PFS [10]. With regard to ICI therapy for HCC, Hung et al reported that NLR ≤ 2.5 was a useful predictor of response to SD or better in 45 patients treated with nivolumab monotherapy, which is similar to our report [19]. On the other hand, Dharmapuri et al reported that NLR after three cycles of nivolumab treatment was more strongly associated with the response and OS prolongation compared with NLR before treatment in 103 patients with HCC treated with nivolumab.…”
Section: Discussionsupporting
confidence: 88%
“…prior to ICI treatment had a better chance of disease-control. 21 In the present study, NLR ≤ 2.74 was associated with an OR to ATZ + BV treatment with both RECIST and mRECIST. These results…”
Section: Discussionsupporting
confidence: 49%
“…[17][18][19] NLR has also been recognized as a predictor of immune checkpoint inhibitor (ICI) therapy in several cancers. 20,21 The aim of this study was to assess the safety and efficacy of ATZ + BV therapy in patients with u-HCC from the viewpoint of their clinical features, including hepatic function, history of MTA therapy, and NLR.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the additional inflammatory indices that are easily acquired should be integrated into the survival prediction model, such as neutrophil-to-lymphocyte ratio. 8,9 Moreover, some indices reflecting liver function are important predictors of prognosis for patients with HCC, which help to build a more comprehensive and accurate prediction model.Last, but not least, since the characteristics of patients with HCC are heterogeneous in terms of liver function, treatment line and type of immunotherapy, subgroup analysis should be generally conducted to evaluate the effectiveness of using the CRAFITY score. The results of subgroup analysis will adequately reflect the predictive performance in different subgroups.In conclusion, the flaws do not detract from the jade's essential beauty.…”
mentioning
confidence: 99%
“…On the other hand, the additional inflammatory indices that are easily acquired should be integrated into the survival prediction model, such as neutrophil-to-lymphocyte ratio. 8,9 Moreover, some indices reflecting liver function are important predictors of prognosis for patients with HCC, which help to build a more comprehensive and accurate prediction model.…”
mentioning
confidence: 99%